Trained Immunity: An Underlying Driver of Inflammatory Atherosclerosis - Zhong, Chao; Yang, Xiaofeng; Feng, Yulin; Yu, Jun (Frontiers in Immunology, 2020)
Atherosclerosis, a chronic inflammatory disease of the arterial wall, is among the leading causes of morbidity and mortality worldwide. The persistence of low-grade vascular inflammation has been considered to fuel the development of atherosclerosis. However, fundamental mechanistic understanding of the establishment of non-resolving low-grade inflammation is lacking, and a large number of atherosclerosis-related cardiovascular complications cannot be prevented by current therapeutic regimens. Trained immunity is an emerging new concept describing a prolonged hyperactivation of the innate immune system after exposure to certain stimuli, leading to an augmented immune response to a secondary stimulus. While it exerts beneficial effects for host defense against invading pathogens, uncontrolled persistent innate immune activation causes chronic inflammatory diseases. In light of the above, the long-term over-activation of the innate immune system conferred by trained immunity has been recently hypothesized to serve as a link between non-resolving vascular inflammation and atherosclerosis. Here, we provide an overview of current knowledge on trained immunity triggered by various exogenous and endogenous inducers, with particular emphasis on its pro-atherogenic effects and the underlying intracellular mechanisms that act at both the cellular level and systems level. We also discuss how trained immunity could be mechanistically linked to atherosclerosis from both preclinical and clinical perspectives. This review details the mechanisms underlying the induction of trained immunity by different stimuli, and highlights that the intracellular training programs can be different, though partly overlapping, depending on the stimulus and the biological system. Thus, clinical investigation of risk factor specific innate immune memory is necessary for future use of trained immunity-based therapy in atherosclerosis.